MINERS’ OPINIONS REGARDING THE INFLUENCE OF THE UNIONS OVER THE SOCIO-ECONOMICAL CONDITIONS IN THE JIU VALLEY - VASILE CIOCODEICĂ; ROBERT PRODANCIUC (Annals of the University of Petrosani: Economics)
In this paper we tried to capture several realities that are present in the Jiu Valley and also tried to have a deeper comprehension of them by analyzing the present reality through the premises set by the past actions. The first step was to present the general situation of the Romanian union world. After that, we used a historical perspective over the present situation of the mining unions in the Jiu Valley and their becoming. We ended the paper with some conclusions drew from a research on a representative sample of miners from the Jiu Valley mines. We statistically analyzed their perceptions regarding the way they feel about the unions and came up with some pretty interesting conclusions.